Mesomorphic properties of cyanobiphenyl dimers with a central malonate unit. Issue 11 (2nd September 2018) - Grunwald, Marco André; Haenle, Johannes Christian; Kreß, Katharina Christina; Forschner, Robert; Wöhrle, Tobias; Frey, Wolfgang; Giesselmann, Frank; Laschat, Sabine
ABSTRACT: A series of cyanobiphenyl dimers attached via alkoxy spacers to a central malonate were prepared, and the mesomorphic behaviour was studied by differential scanning calorimetry (DSC), polarised optical microscopy and X-ray diffraction (Wide-angle X-ray scattering and Small-angle X-ray scattering). Depending on spacer lengths and substitution of the malonate, nematic and smectic A mesophases with pronounced odd–even effect were observed. C-2-unsubstituted malonates formed nematic phases for chain lengths C6 –C14, while C12 and C14 homologues displayed additional smectic A phases. In contrast, malonates with fluorinated tails at C-2 displayed exclusively smectic A phases. Remarkably, the X-ray diffraction profile of the smectic A phase of the C-2-unsubstituted C12 malonate showed a fundamental (001) and the corresponding third-order (003) diffraction peak, but no (002) reflection. Using Fourier analysis, the diffraction pattern was converted to an electron density profile, which was in good agreement with the proposed packing model of the SmA mesophase based on a horseshow- or hairpin-like conformation of the malonate. Graphical Abstract: